2007
DOI: 10.1093/cercor/bhm040
|View full text |Cite
|
Sign up to set email alerts
|

Rising Sound Intensity: An Intrinsic Warning Cue Activating the Amygdala

Abstract: Human subjects overestimate the change of rising intensity sounds compared with falling intensity sounds. Rising sound intensity has therefore been proposed to be an intrinsic warning cue. In order to test this hypothesis, we presented rising, falling, and constant intensity sounds to healthy humans and gathered psychophysiological and behavioral responses. Brain activity was measured using event-related functional magnetic resonance imaging. We found that rising compared with falling sound intensity facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
174
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(192 citation statements)
references
References 51 publications
18
174
0
Order By: Relevance
“…This is probably because of the block design used in that study, which may have led to habituation effects. Indeed, a more recent study by the same group using the same stimuli and an event-related design demonstrates that looming sounds elicit greater activity in auditory cortical areas in the temporal plane (but outside Heschl's gyrus, or primary auditory cortex) than do receding sounds (Bach et al, 2007), consistent with our present results. However, it is not clear whether the lateral belt area in our study is homologous to the temporal plane activation seen by Bach et al (2007).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is probably because of the block design used in that study, which may have led to habituation effects. Indeed, a more recent study by the same group using the same stimuli and an event-related design demonstrates that looming sounds elicit greater activity in auditory cortical areas in the temporal plane (but outside Heschl's gyrus, or primary auditory cortex) than do receding sounds (Bach et al, 2007), consistent with our present results. However, it is not clear whether the lateral belt area in our study is homologous to the temporal plane activation seen by Bach et al (2007).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, a more recent study by the same group using the same stimuli and an event-related design demonstrates that looming sounds elicit greater activity in auditory cortical areas in the temporal plane (but outside Heschl's gyrus, or primary auditory cortex) than do receding sounds (Bach et al, 2007), consistent with our present results. However, it is not clear whether the lateral belt area in our study is homologous to the temporal plane activation seen by Bach et al (2007). This is in large part because of the lack of comparative anatomical data examining the similarities and differences between the auditory cortices [beyond the core region (Hackett et al, 2001)] of monkeys, apes, and humans.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The contrast between sounds increasing vs. decreasing in intensity, however, revealed a different network, including superior temporal sulcus and amygdala, which may reflect a warning process for approaching objects (4,9,20). A more recent fMRI Significance Previous studies demonstrated "auditory looming bias" exclusively by manipulating overall sound intensity.…”
mentioning
confidence: 99%
“…The phenomenon that approaching sounds are more salient than receding sounds is commonly termed "auditory looming bias." Looming bias is reflected in a broad variety of psychophysical tasks related to salience and alertness: bias in loudness-change estimates (2-4) and judgments of duration (5), improved discriminability of motion speed (6), underestimated distances for egocentrically moving (4) or bypassing sounds (7,8), and reduced reaction time for auditory (3,9) and visual (3) targets preceded by looming sounds. In animals, looming biases result in faster learning speed during associative conditioning (10) and longer duration of attention (11).…”
mentioning
confidence: 99%